The Contribution of Social Norms and Big Five Personality Traits of Phubbing Behavior among Senior High School Students in Padang City - Kanaya Yose Putri; Dina Sukma; Zadrian Ardi; Miftahul Fikri (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Phubbing behavior is increasingly common among adolescents as smartphone use rises, and has the potential to disrupt the quality of social interactions and student development. This study aims to analyze the contributions of social norms and the Big Five personality traits to phubbing behavior among high school students in Padang City, both in partial and in simultaneous models. The study used a quantitative approach with an associative design, involving 322 eleventh-grade students selected through purposive and proportionate random sampling techniques. Data were collected using the phubbing behavior scale, social norms scale, and Big Five personality traits scale, which showed acceptable validity, and then analyzed using a multiple regression model in SmartPLS. The results showed that social norms contributed positively and significantly to phubbing behavior (t = 10.486, p < 0.001). Partially, conscientiousness, agreeableness, and neuroticism contributed significantly, while openness and extraversion did not. Simultaneously, social norms and the Big Five personality traits explain 37.8% of the variance in phubbing behavior (R² = 0.378). These findings support an integrative perspective that views phubbing as the result of interactions between social and personality factors and offer practical implications for guidance and counseling interventions that focus on the socialization of social norms and students' personality characteristics. Keywords: phubbing, social norms, big five personality traits, students